2020
DOI: 10.1099/jmm.0.001241
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of etomidate against growing biofilms of fluconazole-resistant Candida spp. strains, binding to mannoproteins and molecular docking with the ALS3 protein

Abstract: This study evaluated the effect of etomidate against biofilms of Candida spp. and analysed through molecular docking the interaction of this drug with ALS3, an important protein for fungal adhesion. Three fluconazole-resistant fungi were used: Candida albicans, Candida parapsilosis and Candida tropicalis. Growing biofilms were exposed to etomidate at 31.25–500 µg ml−1. Then, an ALS3 adhesive protein from C. albicans was analysed through a molecular mapping technique, composed of a sequence of algorithms to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In a previous study, Do Av Sá et al . [15] observed that etomidate exhibited promising activity against the formation of biofilms of fluconazole-resistant C. albicans . Molecular docking experiments demonstrated that etomidate attaches to the same region of the ALS3 complex ligand (heptathreonine), and was close to the residues of the catalytic triad (Ser170) and to the amino acid residue, which had an adhesion function (Lys59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, Do Av Sá et al . [15] observed that etomidate exhibited promising activity against the formation of biofilms of fluconazole-resistant C. albicans . Molecular docking experiments demonstrated that etomidate attaches to the same region of the ALS3 complex ligand (heptathreonine), and was close to the residues of the catalytic triad (Ser170) and to the amino acid residue, which had an adhesion function (Lys59).…”
Section: Discussionmentioning
confidence: 99%
“…Etomidate has reported activity against biofilms of fluconazole-resistant C. albicans [14,15] and MRSA [16]. However, there is no description of its activity against polymicrobial biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) was used to better visualize the effect of SER on microscopic biofilm structures [16]. The C. auris strain was chosen as representative because of its clinical relevance.…”
Section: Methodsmentioning
confidence: 99%
“…The biofilm preventive effect of SER was evaluated according to Xie et al [15] and Sá et al [16], with modifications. Briefly, the microorganisms were prepared as described in the previous section, then the inoculum (100 µl) was added to each well of 96-well plates and incubated for different times (6, 12, 24 and 48 h) at 35 °C together with 100 µl SER at different concentrations (MIC/2, MIC, 2×MIC, 4×MIC and 8×MIC for each strain) diluted in RPMI 1640 in order to evaluate the time that each SER concentration starts to be effective in inhibiting the number of metabolically active cells in the biofilm.…”
Section: Investigation Of the Preventive Potential Of Ser Against Can...mentioning
confidence: 99%
“…The hypnotic agent, etomidate, works against the biofilm of fluconazole-resistant Candida spp. strains [109]. The antiseptic alexidine [103] and the finasteride used to treat the prostatic hyperplasia [110] were highly active in vitro at preventing C. albicans biofilms.…”
Section: Albicans Biofilmsmentioning
confidence: 99%